2022
DOI: 10.24221/jeap.7.01.2022.3963.016-025
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura da comunidade de macroinvertebrados bentônicos em nascentes de fragmentos de Mata Atlântica

Abstract: A Floresta Ombrófila Mista (FOM), fitofisionomia da Mata Atlântica (MA), vem sofrendo redução de sua área original a pequenos fragmentos florestais, o que promove impactos na biodiversidade e no ambiente. As nascentes de água existentes nesses fragmentos desempenham papel crucial para a manutenção dos serviços ecossistêmicos prestados por esse bioma, que fornecem os recursos hídricos necessários ao abastecimento de cidades. Dentre os organismos presentes nesses ecossistemas aquáticos destacam-se os macroinvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Simões et al (2023) found a predominance of chironomids in lotic and lentic environments due to their tolerance to extreme conditions and their detritivorous and collecting eating habits. Hagemeyer et al (2022) found similar results, with a higher abundance of Oligochaeta and Chironomidae organisms in springs that present organic matter in the sediment due to their diet.…”
Section: Water Quality and Surroundings For S Ystemic Management Of S...supporting
confidence: 68%
“…Simões et al (2023) found a predominance of chironomids in lotic and lentic environments due to their tolerance to extreme conditions and their detritivorous and collecting eating habits. Hagemeyer et al (2022) found similar results, with a higher abundance of Oligochaeta and Chironomidae organisms in springs that present organic matter in the sediment due to their diet.…”
Section: Water Quality and Surroundings For S Ystemic Management Of S...supporting
confidence: 68%